Word Divine Guruvak: Gleanings from Sri Guru Granth Saheb - K S Duggal; DUGGAL (K S) (New Delhi UBS Publishers Distributors Ltd, 1999)
Shabds from the Guru Granth Sahib of the Sikhs. Transcreated by Kartar Singh Duggal, to mark tercentenary of the birth of the Khalsao. the page numbers of each selection from the Granth given at foot of each translation
Keywords: Sikkhism; Religion; Devotional Calendar